Different combinations of sodium monensin and virginiamycin during feedlot finishing of Nellore cattle - Rigueiro, A. L.N. [UNESP]; Pereira, M. C.S. [UNESP]; Squizatti, M. M. [UNESP]; Ferreira, M. M. [UNESP]; Dondé, S. C. [UNESP]; Luiz, F. P. [UNESP]; Silvestre, A. M. [UNESP]; Muller, L. R. [UNESP]; Garcia, C. P. [UNESP]; Bueno, A. P.D. [UNESP]; Toledo, L. V. [UNESP]; Estevam, D. D. [UNESP]; et al. (CSIRO Publishing, 2020)
Context: The use of two feed additives, to maximise rumen fermentation, in finishing diets offered to feedlot cattle may positively impact performance. Aims: This study, conducted at the São Paulo State University feedlot, Botucatu campus, Brazil, was designed to evaluate the effects of the combined use of monensin (MON; 30 mg/kg of dry matter; (DM)) and virginiamycin (VM; 25 mg/kg of DM) in high-concentrate diets during the adaptation and finishing periods on feedlot performance, carcass traits, feeding behaviour, blood gas profile, rumen morphometrics and apparent total tract digestibility of nutrients of Nellore cattle. Methods: The experiment was designed as a completely randomised block, replicated six times (3 bulls/pen), in which 72 20 months of age yearling Nellore bulls (388.0 ± 31.1 kg) were fed in 24 pens for 90 days according to the treatments: (1) MON during the entire feeding period (T1), (2) MON + VM during adaptation and only VM during the finishing period (T2), (3) MON + VM during the entire feeding period (T3), and (4) VM during the adaptation and MON + VM during the finishing period (T4). The adaptation program consisted of ad libitum feeding of three diets over the adaptation period of 19 days with concentrate level increasing from 69% to 84% of diet DM. Key results: Overall, bulls fed on T2 had a greater DM intake (P < 0.01), final bodyweight (P = 0.04), average daily gain (P = 0.03), hot carcass weight (P < 0.01), final Longissimus muscle area (P = 0.05), Longissimus muscle area daily gain (P = 0.01), improved carcass G:F (P < 0.01) and increased dressing percentage (P < 0.01). Similarly, bulls fed on T2 were faster to consume 1 kg of either DM (P < 0.01) or neutral detergent fibre (P < 0.01) after 60 days on feed. Furthermore, bulls fed on T2 presented a greater (P = 0.05) cell proliferation index in the rumen papillae. Conclusions: According to the results, Nellore yearling bulls should be fed high-concentrate diets containing MON and VM during adaptation, and only VM during the finishing period to improve overall feedlot performance. Implications: The use of both MON and VM proved to be helpful only during the adaptation period.
Keywords: antibiotic; ionophore; papillae; rumen; starch